Povidone-Iodine 3.35% Solution versus Normal Saline for Irrigation in Lumbar Fusion Surgery: A Retrospective Study - Ahmad FA Allam (Egyptian Spine Association, 2019)
Background Data: Povidone-iodine is very effective broad spectrum antiseptic solution against different types of pathogens including methicillin-resistant Staphylococcus aureus and some strains of Enterococcus faecium based on the antiseptic properties of iodine. Purpose: To evaluate the effect of intraoperative 3.35 % povidone-iodine irrigation in lumbar spine fusion surgeries. Study Design: Retrospective clinical case study. Patients and Methods: 93 spine fusion surgeries in 2016 (Group I) and 112 fusion surgeries in 2017 (Group II). Both groups were retrospectively compared regarding infection rate, fusion rate, and Oswestry Disability Index (ODI) score. Group I had intraoperative saline irrigation and Group II was irrigated with 3.35 % povidone-iodine. Results: There were no reported infections in Group II. Two superficial and two deep wound infections were observed in Group I. Complete wound dehiscence was found in one patient with deep wound infection. The pathogens were methicillin-resistant Staphylococcus aureus in two cases, Klebsiella pneumonia in one case, and combination of methicillin-sensitive Staphylococcus aureus and Staphylococcus epidermidis in the last case. There was insignificant difference between the two groups in fusion rates and with no linear correlation relationship between povidone-iodine soaking time and the fusion rate in Group II. There was significant postoperative ODI improvement in the two groups relative to the preoperative scores with insignificant statistical difference when comparing this improvement of the two groups. Conclusion: Povidone-iodine 3.35% irrigation in lumbar spine fusion surgery is effective in decreasing postoperative infection with no negative influence on the fusion rate or clinical outcome. (2019ESJ177)